2015
DOI: 10.15654/tpk-140357
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic location of the femoral footprint of the cranial cruciate ligament in dogs

Abstract: The reported data can be used to plan and verify the placement of the femoral tunnel opening for intra-articular anatomic CrCL repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Based on the available footprint dataset, our observations indicated that half of femoral CrCL footprints manifest an arrowhead shape, aligning with previous reports that have documented the presence of this particular shape at the femoral CrCL footprints 15 , 26 . A similar shape was also observable at the tibial site (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on the available footprint dataset, our observations indicated that half of femoral CrCL footprints manifest an arrowhead shape, aligning with previous reports that have documented the presence of this particular shape at the femoral CrCL footprints 15 , 26 . A similar shape was also observable at the tibial site (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The procedure for establishing the dataset in the study was inspired by the work of Pillet et al 14 , who conducted a similar experimental approach to quantitatively extract the endpoints of human knee ligaments. In contrast to previous methodologies that focused on estimating footprint centroid positions 12 , 14 , 15 , we developed an SSM-based prediction method that directly estimates footprint contours based on individual bone shapes. This is achieved by propagating the changes in bone shapes to the deformation and positional adjustments of the ligament footprint contours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the dog, insertions of the CCL on the femur and tibia have been assumed to be isometric, reduced to a single point, and projected onto the lateral aspect of the stifle to identify isometric points for both intracapsular 34 and extracapsular repair 35 of the ruptured CCL. In humans, cadaveric studies using various techniques in intact and anterior cruciate ligament deficient knees have concluded that no two points are absolutely isometric; however, near isometry can be defined within certain limits.…”
Section: Discussionmentioning
confidence: 99%